Global Warming Effects Adaptation and Mitigation Strategies - Kaur, Ramanjit; Dass, Anchal; Sepat, Seema; Rana, K. S. (Indian Farming, 2015)
The impact of different climatic factors on agriculture that could arise from the direct effects of increased atmospheric CO2, from effects of changes in climatic and, in coastal regions, from sea-level rise is likely to be extremely complex. They certainlyvary from region to region and from one type of farming to another. Due to complexity of crop environment interactions a multidisciplinary approach to the problem is required in which plant breeders, agronomists, crop physiologists andagrometeorologists need to interact for finding long term solutions in sustaining agricultural production. If the increasing rates of CO2 concentrations above the danger limits are not checked it will lead to irreparable damages to the mankind.However, we are to improve our understanding of the significance of interactive behaviour of increased CO2 concentrations with other climatic changes and its effect on agriculture, then further research into how the mankind can best adapt to, avoid or even profit from such interactions need to be carried out.